Nivel de estrés laboral en estudiantes de internado de enfermería de la Universidad Nacional de Loja - Sanchez Loayza, Santiago Israel (2022)
Work stress is a worrying situation faced by health professionals, which affects their performance and care of patients. To address this problem, the general objective was to analyze the level of work stress in nursing interns at the Universidad Nacional de Loja. The study was carried out with a quantitative, descriptive and cross-sectional approach. The sample consisted of 67 participants who underwent their internship in different health institutions in the town. A survey, based on the "The Nursing Stress Scale" (NSS), was used as an instrument, this tool consists of 34 items that describe different situations that are triggers of stress. In terms of socio-demographic factors, 54% of the population are women, with the age range between 18 and 24 years being predominant, 86.6% are single, and 61.2% reside in urban areas. Regarding the level of stress 70.1% of the population studied presented a low stress level, however, there are 30% that have a medium and high stress level respectively. According to the sociodemographic characteristics of the participants, it was determined that there is a low level of stress, and it was presented mainly in women (58.2%); in ages ranging from 18 to 24 years (35.8%); in singles (61.2%), residents in the urban area (37.3%). In order to deal with this problem, and given that a segment of the population presents an average stress (26.9%) and high stress (3%), a proposal was developed to address stress in the study population. With the results found, it is concluded that there is a low percentage with stress level in the students of the nursing internship, however it is important to consider the risks and complications to which they may be exposed. Keywords: Scale, students, boarding, nurse, risk.